2021
DOI: 10.3390/nu13072138
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Dietary Vitamin D in Individuals with Class II and III Obesity: Prevalence and Association with Metabolic Syndrome

Abstract: The association between vitamin D deficiency and metabolic syndrome (MS) in severe obesity is unclear and controversial. We analyzed serum and dietary vitamin D and their association with MS in 150 adults with class II and III obesity (BMI ≥ 35 kg/m2) from the DieTBra Trial (NCT02463435). MS parameters were high fasting blood glucose, low HDL cholesterol, high triglycerides, elevated waist circumference, and hypertension. Vitamin D deficiency was considered as a level < 20 ng/mL. We performed multivariate P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Although several studies have addressed some factors associated with vitamin D deficiency, there is no consensus about these associations. A cross-sectional study conducted in Brazil demonstrated the low prevalence of vitamin D deficiency in severe obesity (10%) and also identified that serum and dietary vitamin D were not associated with metabolic syndrome [ 71 ]. Therefore, more research is needed on these factors to guide public health policies in the development of action plans to reduce the rate of vitamin D deficiency and consequently avoid its negative outcomes in women of childbearing age.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have addressed some factors associated with vitamin D deficiency, there is no consensus about these associations. A cross-sectional study conducted in Brazil demonstrated the low prevalence of vitamin D deficiency in severe obesity (10%) and also identified that serum and dietary vitamin D were not associated with metabolic syndrome [ 71 ]. Therefore, more research is needed on these factors to guide public health policies in the development of action plans to reduce the rate of vitamin D deficiency and consequently avoid its negative outcomes in women of childbearing age.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the MetS+ RA patients showed lower serum vitamin D concentrations compared to the MetS− RA patients. On one side, this phenomenon could be due to the sequestration of vitamin D in the adipose tissue, which causes the lower bioavailability of this hormone, which is particularly emphasized when the BMI increases [ 46 , 47 ]. On the other hand, there is increasing knowledge that vitamin D not only exerts action on the skeletal mass but also displays extra-skeletal effects, particularly in the modulation of the immune response by downregulating T helper 1 (Th1)-dependent reactivity and by increasing anti-inflammatory cytokine production (IL4, IL-10) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to changes in lifestyle, overweight and obesity are rapidly increasing and reaching epidemic proportions worldwide ( Silveira et al, 2021 , Andersen et al, 2016 ). Obesity is associated with several metabolic abnormalities including insulin resistance, hypertension, non-alcoholic fatty liver disease, type 2 diabetes, metabolic syndrome and cardiovascular diseases (CVDs) ( Kwon et al, 2021 , Engin, 2017 ) as well as a decline in life expectancy ( Janssen et al, 2021 , Blüher, 2019 ).…”
Section: Introductionmentioning
confidence: 99%